Akt and Src mediate the photocrosslinked fibroin-induced neural differentiation. Issue 10 (10th July 2020) - Moysenovich, Anastasia M.; Tatarskiy, Viktor V.; Yastrebova, Margarita A.; Bessonov, Ivan V.; Arkhipova, Anastasia Yu; Kolosov, Andrey S.; Davydova, lyubov I.; Khamidullina, Alvina I.; Bogush, Vladimir G.; Debabov, Vladimir G.; Shaitan, Konstantin V.; Shtil, Alexander A.; et al.
Abstract : Neural transplantation is a promising modality for treatment of neurodegenerative diseases, traumatic brain injury and stroke. Biocompatible scaffolds with optimized properties improve the survival of transplanted neural cells and differentiation of progenitor cells into the desired types of neurons. Silk fibroin is a biocompatible material for tissue engineering. Here, we describe thin-film scaffolds based on photocrosslinked methacrylated silk fibroin (FBMA). These scaffolds exhibit an increased mechanical stiffness and improved water stability. Photocrosslinking of fibroin increased its rigidity from 25 to 480 kPa and the contact angle from 59.7 o to 70.8 o, the properties important for differentiation of neural cells. Differentiation of SH-SY5Y neuroblastoma cells on FBMA increased the length of neurites as well as the levels of neural differentiation markers MAP2 and βIII-tubulin. Growth of SH-SY5Y cells on the unmodified fibroin and FBMA substrates led to a spontaneous phosphorylation of Src and Akt protein kinases critical for neuronal differentiation; this effect was paralleled by neural cell adhesion molecule elevation. Thus, FBMA is an easily manufactured, cytocompatible material with improved and sustainable properties applicable for neural tissue engineering.